Theory Dating and Isnad Cum Matn Harald Motzki in Revealing The Authenticity of The Prophet Hadith - Muh. Ilham R. Kurniawan (Al-Bukhari : Jurnal Ilmu Hadis, 2021)
According to Kamaruddin Amin, the discourse on the authenticity, validity, and reliability of the hadith authentication methodology is the most basic thing in the study of hadith. The doubts of some Muslim scholars over the role of hadith as the second source of authority after the Qur'an, are not entirely related to their rejection of the accuracy of the methodology used in determining the originality of the hadith. If the authentication methodology used is problematic, then all the results achieved from the method are not sterile from the possibility of re-verification, historical criticism and even results can collapse. Doubts also come from the orientalists regarding the authenticity of the hadith. The epistemology of the orientalists with characteristics of skepticism or doubt in terms of testimony and tries to re-question what the hadith really is, is it true that the hadith is the oral speech of the prophet, the prophet's behavior or the perception of the Islamic community about the prophet, is the book of hadith that we inherit from the third century such as Sahih Bukhari and Sahih Muslim, is a reflection of the sunnah of the Prophet? This school of skepticism is represented by Joseph Schacht (Austria) and Ignaz Goldziher (Hungary) and Harald Motzki.